An experts survey on sustainability across twenty-seven extensive European systems of grassland management. - Caballero, Rafael; Gil, Angel; Fernández-Santos, Xavier (Environmental management, 2008)
European Large Scale Grazing Systems (LSGS) are at a crossroad with environmental, agronomic, and social factors interacting on their future viability. This research assesses the current environmental and socio-economic status of a wide range of European LSGS according to an agreed subset of sustainability criteria and indicators, which have been recognized by corresponding experts and privileged observers on their respective case-study system. A survey questionnaire was drafted containing five main criteria (pastoral use, environmental, economic, social, and market and development), with four conceptual-scored variables (indicators) within each criterion. Descriptive, analytical and clustering statistical techniques helped to draw a synthesis of the main result and to standardize sustainability variables across different biogeographical regions and management situations. The results show large multicollinearity among the 20 variables proposed. This dependence was revealed by the reduction to six main factor-components, which accounted for about 73% of the total variance in responses. Aggregation of point-score indicators across criteria to obtain a sustainability index can be of less policy relevance than responses to specific criteria or indicators. Affinity between case-study systems, as judged by collaborative-expert responses, was not related to biogeographical location, operating livestock sector, or population density in their areas. The results show larger weaknesses and constraints in the economic and social criteria than in the pastoral and environmental criteria, and the large heterogeneity of responses appears in the social criterion.
Keywords: European agriculture; Low-input grazing systems; Sustainability indicators